2018
DOI: 10.1007/s13577-018-0214-1
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-215-5p and miR-642a-5p as potential biomarker for diagnosis of osteosarcoma in Mexican population

Abstract: Osteosarcoma is the most common malignant bone neoplasia affecting individuals in the second decade of life. The survival rate has not been improved during the last 25 years, in part because of the lack of specific markers. The microRNAs have been identified as important regulators of gene expression, experimental evidence suggests these molecules as key players in cancer development and progression. To identify miRNAs differentially expressed in serum from patients with osteosarcoma compared to healthy donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…MiR-let-7a, quantified in total blood of osteosarcoma patients, is considered a potential diagnostic (AUC = 0.90) and negative prognostic biomarker for osteosarcoma [281]. In a small Mexican cohort, microarray analysis of 648 serum miRNAs revealed that only miR-642a-5p and miR-215-5p are upregulated in osteosarcoma, with AUC of 0.84 and 0.87 [282].…”
Section: Mirnas As Tumor Biomarkersmentioning
confidence: 99%
“…MiR-let-7a, quantified in total blood of osteosarcoma patients, is considered a potential diagnostic (AUC = 0.90) and negative prognostic biomarker for osteosarcoma [281]. In a small Mexican cohort, microarray analysis of 648 serum miRNAs revealed that only miR-642a-5p and miR-215-5p are upregulated in osteosarcoma, with AUC of 0.84 and 0.87 [282].…”
Section: Mirnas As Tumor Biomarkersmentioning
confidence: 99%
“…The highly dysregulated miR-25-3p correlates with patient prognosis, and might serve as a non-invasive blood-based biomarker for tumor monitoring and prognostic prediction. Correlation between miR-25 expression and bone metabolism was reported previously, with intracellular and extracellular oncogenic functions imputed to miR-25-3p [32,[54][55][56]. Another study conducted a meta-analysis to assess the true diagnostic value of circulating miRNAs for early detection of OS [57].…”
Section: Discussionmentioning
confidence: 77%
“…In addition, TaqMan Low Density Arrays identified 15 miRNAs that are differentially expressed in OS patients compared with healthy controls; of these, miR-215-5p and miR-642a-5p are potential markers for OS diagnosis [32]. Genome-wide profiling identified 56 and 164 c-miRNAs that were upregulated and downregulated, respectively, in OS samples.…”
Section: Discussionmentioning
confidence: 99%
“…miR-26a suppresses osteosarcoma metastasis by targeting HMGA1 [18]. MiR-215-5p and miR-642a-5p may be potential biomarkers for diagnosis of osteosarcoma [19]. And miR-660 promotes osteosarcoma cell proliferation and invasion [20].…”
Section: Discussionmentioning
confidence: 99%